The Role of Tourism Village Development on the Economic Welfare of Local Communities - Mender Dian Febriani Boru Siahaan; Yuliana Rini Hardanti; Josephine Wuri; Laurentius Bambang Harnoto (International Journal Labs, 2026)
This study aims to analyze the role of the development of Sosromenduran Tourism Village in improving the economic welfare of the local community. Sosromenduran Tourism Village, located in the Municipality of Yogyakarta, was developed as a form of community-based tourism by actively involving the community in economic and tourism activities. The approach used in this study is a qualitative descriptive method, with data collection techniques in the form of observation, in-depth interviews, and documentation involving eight informants from three categories, namely the management of Sosromenduran Tourism Village, community members who are involved, and those who are not involved. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawing. The results of the study show that the role of tourism village development has a positive impact on economic welfare indicators, including increased income, job creation, MSME growth, access to training and skills, and the availability of infrastructure and public facilities. In addition, this village also encourages the promotion of local products and cultural preservation through various tourism events. This research emphasizes the importance of community empowerment in creating inclusive and sustainable tourism and shows that Sosromenduran Tourism Village can serve as a model for community-based local economic development. However, challenges are still encountered; limited public participation remains a challenge in itself, and fluctuations in the number of tourists during certain periods can affect income stability.